Probing energy landscapes in multilayer heterostructures: Challenges and opportunities - Scott A. Chambers (APL Materials, 2019)
Quantitative characterization of energy landscapes at buried interfaces is essential for assessing their functionality. This perspective highlights recent developments in reconstructing internal potential profiles based on hard x-ray photoemission experiments that have proved to be a rich source of information. We show that band-edge profiles can be reconstructed from core-level photoelectron spectra by performing a comprehensive search for the best-fit set of associated layer-resolved spectra. The use of hard x-rays allows heterostructures to be probed over length scales comparable to relevant electronic screening lengths. Significantly, this information takes our understanding of such systems to a new level that is not currently achievable using any other experimental technique.